Prcing Maximum Value Options under the Mixed Fractional Brownian Motion with Jumps - Wang, Rong (Journal of Global Economy, Business and Finance, 2024)
In this paper, a semi-closed analytical formula for the values of European call options on the maximum of two-asset options under the Mixed Fractional Brownian Motion model with Jumps (JMFBM) are derived by measure transform and equivalent martingale.